Sensory dominance : an experiment across cultures - Locke, Hester W (Rhodes University, Faculty of Humanities, Department of Psychology, 1977)
Physical and intellectual differences in the home environment of Xhosa and White children suggested that the interaction of touch and vision in situations of sensory conflict and the development of dominance may be different in children from these homes. Children aged 5-13 years were tested on apparatus which created a conflict of tactual and visual judgement about the perceived size of the stimulus. Xhosa and White subjects performed similarly except when only tactual judgement was allowed and the Xhosa group were less influenced by touch. The study concludes that for children touch and vision contribute equally to the resolution of sensory conflict when both senses are active in size-judgements and when only one mode is allowed for judging then the resolution is biased towards this mode. This outcome is different from that of experiments with adults and has implications for theories derived from them.
Keywords: Perception -- Testing; Senses and sensation -- Testing; Dominance (Psychology)